Association Between Eye Color and Postoperative Pain in Female Patients With Symptomatic Irreversible Pulpitis in Mandibular Molars: A Prospective, Parallel-Group, Observational Study - Merve Sarı; Koray Yılmaz (Pain Research and Management)
Conclusion: Pain scores decreased significantly after RCT in both groups on all days (p<0.05). No significant differences were found in the success rate of IANB and postop pain scores between light- and dark-eyed female patients who experienced SIP in a mandibular molar.